A Sustainability Accounting: Case Study on Exploration, Production and Midstream Activities at Maersk Oil - Homayoun, Saeid; Al-Thani, Faisal F.J.; Homayoun, Sakine (International Journal of Energy Economics and Policy, 2016)
This paper gives a short introduction to sustainable accounting and its essential measurement problems. The greatest challenge seems to be how companies should create sustainability reports that achieve the demands for transparency and accuracy. Because the current frameworks vary considerably, the development of standards and guidance to report sustainability will most likely continue to evolve. This study proposes a model to Maersk Company allowing them to use a sustainability accounting framework as guidance for disclosure of material sustainability and accounting metrics to determine sustainability-related risks and opportunities it faces using the sustainability accounting standard for the oil and gas industries, particular to exploration, production and midstream activities. Keywords: Sustainability Accounting, Measurement Problems, Oil and Gas Industries JEL Classifications: M40, Q56, Q54, L72